Political Turmoil: Does Sensus Communis exist in (Post-)Politics? - Aleknavičiūtė, Ineta (Politologija, 2024)
This paper focuses on different concepts of sensus communis and their relationship with the conditions of political reality. An attempt is made to show that Gadamer’s and Arendt’s political conception of sensus communis is too dependent on political conditions and the homogeneity and unity of the community, and thus cannot exist under post-political conditions. The paper seeks to defend Immanuel Kant’s aesthetic conception of sensus communis, demonstrating that the disinterested judgment of beauty exists regardless of political circumstances. Based on this, the paper reviews practices existing in post-politics that attempt to use the aesthetic understanding of sensus communis for the purposes of political unity. It also draws attention to the understanding of sensus communis in different contexts, arguing that the concept and its interpretation often become obscured across various contexts.
Keywords: sensus communis; post-politics; politics; universality